Cephalopod‐Inspired Design of Photomechanically Modulated Display Systems for On‐Demand Fluorescent Patterning (Adv. Mater. 4/2022). Issue 4 (27th January 2022) - Shi, Huihui; Wu, Shuangshuang; Si, Muqing; Wei, Shuxin; Lin, Guoqing; Liu, Hao; Xie, Weiping; Lu, Wei; Chen, Tao
Abstract : Fluorescent Patterning In article number 2107452, Wei Lu, Tao Chen, and co‐workers present a photomechanically modulated fluorescent system that enables on‐demand display of fluorescent patterns under near‐IR light light via photomechanical bending of a fluorescent actuator. This strategy is promising for fabricating on‐demand fluorescent display platforms that combine a wide choice of fluorophores, remote control with high spatial/temporal precision, and single‐input multiple‐output features.